A solvent-free approach to glycosyl amides: toward the synthesis of α-N-galactosyl ceramides. Issue 23 (3rd June 2015) - Chennamadhavuni, Divya; Howell, Amy R.
Graphical abstract: Abstract: A new, simple, and efficient method for the synthesis of both α- and β-glycosyl amides using solvent-free conditions is described. This method involves the coupling of glycosyl amines with the p -nitrophenol esters of lipids as a key step.